Investigation of ash and combustion characteristics during co-combustion of coal and solid recovered fuel in a laboratory-scale combustor - Prismantoko, Adi; Karuana, Feri; Prayoga, Moch Zulfikar Eka; Darmawan, Arif; Muflikhun, Muhammad Akhsin; Sunyoto, Nimas Mayang Sabrina; Zhu, Mingming; Aziz, Muhammad; Hariana, Hariana (Taylor & Francis, 2026)
Population growth and limited landfill area increase the problems associated with municipal solid waste (MSW). The MSW conversion into solid recovered fuel (SRF) improves the calorific value which has the potential to be used as a power plant boiler fuel. This study investigates ash deposition and combustion characteristics during co-combustion of coal and SRF at various dosages (5, 10, 15, 20, and 25 wt%). Thermogravimetry analysis, preliminary risk assessment, and morphology analysis of ash deposits are comprehensively performed. The study reveals that based on combustion performance, SRF blends up to 20 wt% show slightly altered burnout temperatures compared to coal combustion, whereas, at 25 wt%, the combustion temperature increases significantly. On the initial risk assessment, the samples tested have a low to medium risk of slagging. Morphological observations show that fine, irregular, and unmelted particles dominate coal ash deposits, while SRF ash deposits are dominated by melted and agglomerated particles. The melted particles gradually increase as the dosage of SRF in the mixture increases. Low melting temperature element-rich particles start to be observed at doses higher than 10 wt%. At 25 wt% SRF blends, material degradation is observed with the presence of Cr in the ash deposit. Overall, co-combustion over 10 wt% SRF shows results that should be considered, particularly the increase in sintering ash that can cause problems in the boiler pipes. This study provides insight into the optimum dosage suitable for blending SRF and coal in power plant boilers.
Keywords: 4004 Chemical Engineering; 40 Engineering; Energy